Podocytopenia in Diabetic Nephropathy: A Role for the Thromboxane A2 TP Receptor - Bugnot, Gwendoline Carine Denise (Université d'Ottawa / University of Ottawa, 2013)
Although the etiology of diabetic nephropathy is still uncertain, proteinuria due to podocyte injury and loss (podocytopenia) are early features of the disease. Significant increases in thromboxane A2 (TXA2) production as well as expression of its receptor in animal models of diabetic nephropathy led to the hypothesis that TXA2 acting via its thromboxane-prostanoid (TP) receptor induces podocytopenia resulting in proteinuria. Systemic infusion of a TP antagonist demonstrated an important role of TXA2/TP signalling in our model of streptozotocin induced type-1 diabetic nephropathy by reducing kidney damage including proteinuria. Podocyte specific TP overexpressing mice did not demonstrate more pathologic or dynamic kidney damage than non-transgenic mice in STZ-induced diabetic nephropathy. Further assessment of the TP transgene functionality in this mice line is necessary to validate those results. Whereas the importance of TXA2/TP signalling is undeniable in diabetic nephropathy, it appears that podocyte TP receptors might not be directly targeted.
Keywords: Podocyte; Diabetic nephropathy; TP receptor; Thromboxane A2; Proteinuria; SQ29548; Arachidonic acid